Performance-guaranteed adaptive self-healing control for wastewater treatment processes. (August 2022) - Du, Peihao; Peng, Xin; Li, Zhongmei; Li, Linlin; Zhong, Weimin
Abstract: This paper investigates the performance-guaranteed adaptive self-healing control for wastewater treatment processes (WWTPs), in which the non-ideal actuator, i.e., the actuator suffering from faults and constraints is considered. Firstly, an error conversion dynamic model based on a new prespecified-time performance function is presented to guarantee that the tracking error is quickly maintained in the user-defined area regardless of the occurrence of actuator faults and constraints. Secondly, a novel smooth approximation function is constructed to imitate the non-smooth characteristics of actuator constraints. Thirdly, the unknown bounds of non-ideal actuator parameters are estimated online in place of parameters themselves. Meanwhile, the lumped disturbances induced by the external disturbance and the fuzzy approximation error are suppressed via H ∞ control theory. In addition, the stability analysis is carried out by the Lyapunov stability criterion to guarantee that all closed-loop system signals are bounded. Finally, comparative simulation results demonstrate that the proposed method has the superiorities in terms of preferable dynamic tracking performance with fast transient convergence, strong robustness and performance recovery under non-ideal actuator. Highlights: Smooth approximation function is designed to simulate the constraint characteristic of WWTP actuator. Error conversion dynamic model using prespecified-time performance function is constructed. Unknown bounds of non-ideal actuator parameters are estimated online. Performance-guaranteed adaptive self-healing controller is proposed.